Changes in the Women's Body During the Climate Period (Texas Journal of Medical Science, 2022)
The period of climacteric syndrome is a physiological process in women from 40 to 65-70 years, the period of invalidity in the reproductive period is dominated by estrogen deficiency in women. This article is about changes in the female body during menopause